Komunikacja marketingowa czasu pandemii na podstawie portalu społecznościowego Facebook - Smól, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*66.02px); top: calc(var(--scale-factor)*118.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0179);" role="presentation">Communications made by <span dir="ltr" style="left: calc(var(--scale-factor)*175.57px); top: calc(var(--scale-factor)*118.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01018);" role="presentation">marketing specialists during the <span dir="ltr" style="left: calc(var(--scale-factor)*307.02px); top: calc(var(--scale-factor)*119.55px); font-size: calc(var(--scale-factor)*8.60px); font-family: serif; transform: scaleX(1.10161);" role="presentation">COVID<span dir="ltr" style="left: calc(var(--scale-factor)*337.19px); top: calc(var(--scale-factor)*118.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00585);" role="presentation">-19 pandemic dif<span dir="ltr" style="left: calc(var(--scale-factor)*66.33px); top: calc(var(--scale-factor)*132.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.987018);" role="presentation">fer greatly from the journalistic communications creating a <span dir="ltr" style="left: calc(var(--scale-factor)*301.03px); top: calc(var(--scale-factor)*132.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.985734);" role="presentation">climate <span dir="ltr" style="left: calc(var(--scale-factor)*332.04px); top: calc(var(--scale-factor)*132.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.981931);" role="presentation">of fear. Companies <span dir="ltr" style="left: calc(var(--scale-factor)*66.45px); top: calc(var(--scale-factor)*146.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.06281);" role="presentation">are trying to <span dir="ltr" style="left: calc(var(--scale-factor)*121.48px); top: calc(var(--scale-factor)*146.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03986);" role="presentation">exert a <span dir="ltr" style="left: calc(var(--scale-factor)*152.55px); top: calc(var(--scale-factor)*146.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03119);" role="presentation">positive influence on <span dir="ltr" style="left: calc(var(--scale-factor)*242.12px); top: calc(var(--scale-factor)*146.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.05471);" role="presentation">customer attitudes and draw their atten<span dir="ltr" style="left: calc(var(--scale-factor)*66.32px); top: calc(var(--scale-factor)*160.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03985);" role="presentation">tion <span dir="ltr" style="left: calc(var(--scale-factor)*84.47px); top: calc(var(--scale-factor)*160.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02185);" role="presentation">to <span dir="ltr" style="left: calc(var(--scale-factor)*94.39px); top: calc(var(--scale-factor)*160.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.982297);" role="presentation">the marketing offering by <span dir="ltr" style="left: calc(var(--scale-factor)*196.86px); top: calc(var(--scale-factor)*160.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.99766);" role="presentation">neutralising their sense of threat and informing them <span dir="ltr" style="left: calc(var(--scale-factor)*66.36px); top: calc(var(--scale-factor)*174.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03775);" role="presentation">of protective measures taken and of the potential health benefits of purchasing the <span dir="ltr" style="left: calc(var(--scale-factor)*66.43px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00994);" role="presentation">products offered or the service provided. The constant trends are to <span dir="ltr" style="left: calc(var(--scale-factor)*339.87px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.974473);" role="presentation">use allusive state<span dir="ltr" style="left: calc(var(--scale-factor)*66.31px); top: calc(var(--scale-factor)*202.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02329);" role="presentation">ments and tabooisation <span dir="ltr" style="left: calc(var(--scale-factor)*163.22px); top: calc(var(--scale-factor)*202.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00321);" role="presentation">of the language sphere associated with the pandemic. One of <span dir="ltr" style="left: calc(var(--scale-factor)*66.32px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.969543);" role="presentation">the factors that can help attract a <span dir="ltr" style="left: calc(var(--scale-factor)*194.10px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.972072);" role="presentation">potential customer is humour, which creates a <span dir="ltr" style="left: calc(var(--scale-factor)*373.95px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.991538);" role="presentation">distance <span dir="ltr" style="left: calc(var(--scale-factor)*66.33px); top: calc(var(--scale-factor)*230.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02399);" role="presentation">from the hazard. This article presents the various roles played by <span dir="ltr" style="left: calc(var(--scale-factor)*334.64px); top: calc(var(--scale-factor)*230.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00647);" role="presentation">marketing special<span dir="ltr" style="left: calc(var(--scale-factor)*66.29px); top: calc(var(--scale-factor)*244.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.999346);" role="presentation">ists in a <span dir="ltr" style="left: calc(var(--scale-factor)*99.35px); top: calc(var(--scale-factor)*244.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00575);" role="presentation">pandemic-triggered crisis situation <span dir="ltr" style="left: calc(var(--scale-factor)*241.55px); top: calc(var(--scale-factor)*244.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.999557);" role="presentation">(e.g. the role of the victim, the role of the <span dir="ltr" style="left: calc(var(--scale-factor)*66.45px); top: calc(var(--scale-factor)*258.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01907);" role="presentation">saviour who provides safety, health and good <span dir="ltr" style="left: calc(var(--scale-factor)*253.61px); top: calc(var(--scale-factor)*258.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02683);" role="presentation">mood). The study examines the posts <span dir="ltr" style="left: calc(var(--scale-factor)*66.43px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0209);" role="presentation">published on <span dir="ltr" style="left: calc(var(--scale-factor)*121.31px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.978708);" role="presentation">Facebook pages by <span dir="ltr" style="left: calc(var(--scale-factor)*198.76px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00977);" role="presentation">randomly selected companies between October and <span dir="ltr" style="left: calc(var(--scale-factor)*66.03px); top: calc(var(--scale-factor)*286.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.98667);" role="presentation">December 2020.